Oxidative stress and dysregulated long noncoding RNAs in the pathogenesis of Parkinson’s disease - Jialu Wang; Meitong Liu; Jiuhan Zhao; Pan Hu; Lianbo Gao; Shen Tian; Jin Zhang; Huayan Liu; Xiaoxue Xu; Zhenwei He (Biological Research)
Abstract Parkinson’s disease (PD) is a progressive age-related neurodegenerative disease whose annual incidence is increasing as populations continue to age. Although its pathogenesis has not been fully elucidated, oxidative stress has been shown to play an important role in promoting the occurrence and development of the disease. Long noncoding RNAs (lncRNAs), which are more than 200 nucleotides in length, are also involved in the pathogenesis of PD at the transcriptional level via epigenetic regulation, or at the post-transcriptional level by participating in physiological processes, including aggregation of the α-synuclein, mitochondrial dysfunction, oxidative stress, calcium stabilization, and neuroinflammation. LncRNAs and oxidative stress are correlated during neurodegenerative processes: oxidative stress affects the expression of multiple lncRNAs, while lncRNAs regulate many genes involved in oxidative stress responses. Oxidative stress and lncRNAs also affect other processes associated with neurodegeneration, including mitochondrial dysfunction and increased neuroinflammation that lead to neuronal death. Therefore, modulating the levels of specific lncRNAs may alleviate pathological oxidative damage and have neuroprotective effects. This review discusses the general mechanisms of oxidative stress, pathological mechanism underlying the role of oxidative stress in the pathogenesis of PD, and teases out the mechanisms through which lncRNAs regulate oxidative stress during PD pathogenesis, as well as identifies the possible neuroprotective mechanisms of lncRNAs. Reviewing published studies will help us further understand the mechanisms underlying the role of lncRNAs in the oxidative stress process in PD and to identify potential therapeutic strategies for PD.